Increase in Body Dimensions of Post-Weaning Female Holstein Friesian Calves Due to the Use of Lactation Cow Concentrate by Calf Starter Substitution - Hartanto, Rudy; Fariha, Nida; Harjanti, Dian Wahyu; Prayitno, Edi; Wahyono, Fajar (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
The aim of the study was to analyze the increase in body dimensions of post-weaning female Holstein Friesian (HF) calves fed with lactation cow concentrate with different levels of calf starter substitution. The material was 4 post-weaning female HF calves aged 4-5 months, with an average weight of 101.38 ± 14.21 kg. The feed consisted of elephant grass, calf starter (CS), and lactation cow concentrate (LCC). The study used a Latin square design, with 4 concentrate treatments, i.e. P1 (75% CS and 25% LCC), P2 (50% CS and 50% LCC), P3 (25% CS and 75% LCC), P4 (100% LCC); and 4 replications in 4 periods (each period in 1 month). The concentrate was given 1% BW in the dry matter; elephant grass and drinking water were provided in a measurable ad libitum. The research parameters were the increase in body dimensions (heart girth (HG), body length (BL), and withers height (WH)). The treatments had no significant effect (p>0.05) on the increase in body dimensions, were P1 (HG = 2.31 cm/month, BL = 4.75 cm/month, WH = 1.95 cm/month), P2 (HG = 4.23 cm/month, BL = 4.38 cm/month, WH = 2.23 cm/month), P3 (HG = 4.60 cm/month, BL = 4.38 cm/month, WH = 2.35 cm/month), P4 (HG = 4,10 cm/month, BL = 3.48 cm/month, WH = 2.18 cm/month). It was concluded that with sufficient quality forage feed, giving 100% LCC to post-weaning female HF calves could result in an increase in body dimensions that was relatively the same as the substitution of CS (25-75%) in LCC as concentrate feed.Keywords: post-weaning female HF calves, body dimensions, calf starter, lactation cow concentrate